Does the level of energy intensity matter in the effect of energy consumption on the growth of transition economies? Evidence from dynamic panel threshold analysis - Aydın, C.; Esen Ö. (Elsevier B.V., 2018)
This study investigates whether the effect of energy consumption on economic growth differs by the level of energy intensity. We employ an advanced dynamic panel threshold regression model to test for the “threshold” level of energy intensity that has an asymmetrical energy consumption effect on economic growth; we consider 12 Commonwealth of Independent States countries over the period 1991–2013. The estimated panel threshold regression model suggests 0.44% as the threshold level of energy intensity. Energy consumption above this level significantly retards economic growth, whereas energy consumption below the level is found to have a statistically significant positive effect on economic growth. Thus, when the threshold level of energy intensity (one of the important indicators of energy efficiency) is exceeded, energy consumption significantly hinders growth. If policy makers pay more attention to energy intensity while formulating new energy policies, substantial gains can be achieved in low energy intensity environments. © 2017 Elsevier B.V.
Keywords: Dynamic panel threshold analysis; Economic growth; Energy consumption; Energy intensity